Association between anxiety level and short-term memory performance among medical students during examinations - Jihan Afifa Hasna; Stri Nareswari; Akhmad Kheru Dharmawan; Marisa Anggraini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Anxiety is a common psychological response experienced by medical students during academic examinations and may influence cognitive functions, including short-term memory, which plays an important role in learning and academic performance. Purpose: To determine the relationship between anxiety level and short-term memory performance during the academic examination phase among Class of 2024 medical students. Method: An observational analytic study with a cross-sectional design was conducted among 130 Class of 2024 medical students selected using a total sampling technique. Anxiety level was measured using the Hamilton Anxiety Rating Scale (HARS), while short-term memory performance was assessed using the Digit Span Backward Test. Data were analysed using descriptive statistics and the Spearman rank correlation test. Results: Most respondents experienced mild anxiety (60.0%) and demonstrated moderate short-term memory performance (60.0%), with no respondents classified as having low memory performance. Spearman rank correlation analysis revealed a very weak positive correlation between anxiety level and short-term memory performance; however, the association was not statistically significant (r = 0.107, p = 0.226). Conclusion: Anxiety level was not significantly associated with short-term memory performance among Class of 2024 medical students during the academic examination phase. These findings suggest that the anxiety experienced by most students remained within an adaptive range and did not substantially affect short-term memory performance. Stress management and psychological support may help students maintain psychological well-being during periods of academic demands. Keywords: Anxiety; Medical Students; Short-Term Memory; Digit Span Backward Test.